Pharmacokinetics of Lapatinib, a Nonrenally Cleared Drug, in Patients With End‐Stage Renal Disease on Maintenance Hemodialysis. (10th May 2019) - Pai, Sudhakar M.; Chaikin, Philip; Berg, Jolene Kay
Abstract: Lapatinib, a tyrosine kinase inhibitor, is approved for the treatment of breast cancer. The literature shows that it is metabolized by CYP3A4 and eliminated predominantly (>90%) by the fecal route, with minimal (<2%) renal elimination in healthy subjects (dose of 250 mg); in cancer patients, renal elimination is minimal at therapeutic doses. For nonrenally cleared drugs, while there is ample evidence of pharmacokinetic alterations secondary to renal impairment‐induced effects on drug metabolizing enzymes and/or transporters, the effect of end‐stage renal disease (ESRD) on lapatinib pharmacokinetics has not been determined. Rather, as stated in the drug's label, the expectation is lack of effect of renal impairment on lapatinib pharmacokinetics based on its minimal renal elimination. The current report addresses this gap with pharmacokinetic data (obtained in a 1‐way drug interaction study) in ESRD patients (n = 11) on maintenance hemodialysis and compared with published data in 37 healthy subjects in 3 separate studies. Following a 250‐mg oral dose in ESRD patients, the median tmax was 3.0 hours, and geometric mean (95%CI) values for Cmax, AUCinf, and t1/2 were 349 ng/mL (245–499 ng/mL), 4410 ng·h/mL (2960–6580 ng·h/mL), and 14.8 hours (9.7–22.5 hours), respectively. These parameters approximated published values in healthy subjects and demonstrated that renal impairment and hemodialysis did not affect lapatinib pharmacokinetics. The results of the present study in this renally impaired population, the only such information available to date, support the drug's label and are valuable in view of the recognized difficulties in enrolling organ‐impaired patients in oncology trials.